2022
DOI: 10.1242/bio.059277
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of Caenorhabditis elegans Haspin-like genes shows that hasp-1 plays multiple roles in the germline

Abstract: Haspin is a histone kinase that promotes error-free chromosome segregation by recruiting the Chromosomal Passenger Complex (CPC) to mitotic and meiotic chromosomes. Haspin remains less well studied than other M-phase kinases and the models explaining Haspin function have been developed primarily in mitotic cells. Here, we generate strains containing new conditional or nonsense mutations in the C. elegans Haspin homologs hasp-1 and hasp-2 and characterize their phenotypes. We show that hasp-1 is responsible for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Timelapse imaging of mNeonGreen::tubulin in bir-1(E69A, D70A) mutants revealed apolar metaphase spindles that shrank without chromosome separation during both meiosis I and meiosis II (Fig 6A) ). Because a hasp-1(null) mutant is completely sterile [46], the low hatch rate suggested that the low frequency of bipolar spindles in HASP-1-depleted worms was due to incomplete depletion by the degron. Because haspin is recruited to chromosomes by cohesin-associated PDS5 [32], these results indicated that the subclass of Aurora B that is recruited to chromosomes by cohesin and haspin-dependent phosphorylation of histone H3 is required for bipolar spindle assembly and that cohesin-independent and haspin-independent Aurora B on chromosome lobes and anaphase microtubules are not sufficient to drive bipolar spindle assembly.…”
Section: Haspin-dependent Aurora B Kinase Is Required For Bipolar Mei...mentioning
confidence: 99%
“…Timelapse imaging of mNeonGreen::tubulin in bir-1(E69A, D70A) mutants revealed apolar metaphase spindles that shrank without chromosome separation during both meiosis I and meiosis II (Fig 6A) ). Because a hasp-1(null) mutant is completely sterile [46], the low hatch rate suggested that the low frequency of bipolar spindles in HASP-1-depleted worms was due to incomplete depletion by the degron. Because haspin is recruited to chromosomes by cohesin-associated PDS5 [32], these results indicated that the subclass of Aurora B that is recruited to chromosomes by cohesin and haspin-dependent phosphorylation of histone H3 is required for bipolar spindle assembly and that cohesin-independent and haspin-independent Aurora B on chromosome lobes and anaphase microtubules are not sufficient to drive bipolar spindle assembly.…”
Section: Haspin-dependent Aurora B Kinase Is Required For Bipolar Mei...mentioning
confidence: 99%